Зголемување на криопрезервацискиот капацитет на ејакулатни медиуми за овчеполска праменка со употреба на семинална плазма и глутатион - Николовски, Мартин (Факултет за ветеринарна медицина, УКИМ, Скопје, 2019)
The complementary effect of protein and antioxidant components of the seminal plasma in regulating oxidative radical concentration was the basic concept of investigating the cryopreserving potential of tris-based (tris-hydorymethyl-aminomethane) media (tris-CM) supplemented with reduced glutathione (GSH) and homologous-seminal-plasma (HSP) in aim of achieving higher cryopreserving (CP potential of ovchepolska pramenka spermatozoa. The aims of this research were: 1. To assess the CP success of ovchepolska pramenka spermatozoa extended in HSP/GSH supplemented tris-CM; 2. To assess the CP success of ovchepolska pramenka spermatozoa extended prior- or following-CP; 3. To assess the optimizing effect of incubation time on HSP/GSH supplemented tris-CM. Single ejaculates were acquired from ten rams (ovchepolska pramenka) with artificial vagina method. Fresh ejaculates were pooled in single volume which was divided in aliqotes-samples (N=240). Four tris-CM were prepared: 1. (С) - HSP and GSH free; 2. (Е1) - with GSH (5 mM); 3. (Е2) - with HSP (20 %); and (Е3) - with GSH (5 mM) and HSP (20 %). One half of the samples were extended prior- (a-CT), and the other following-CP (b-CT). After the CP in liquid nitrogen, the samples were placed in incubation chamber (37°С) and were assessed at 0- and 3-hours incubation. The CP success was assessed according to the degree of retaining structural integrity, morphology (Hancock-2) and motility (CASA – Hamilton Thorne). Interpretation was performed by Pearson’s χ2 test of independence, which was evaluated according to degrees of freedom, probability levels (p < α) and minimal χ2 value, determined algorithmically G*Power v.3.1). E3 in a-CT method at 0-hour incubation had the highest proportion of cells with intact structural integrity and morphology (57.16 %), and retained trajectory linearity of motile cells. C in a-CT method at 0-hour incubation had the highest proportion of cells with deteriorated integrity and morphology (6.82 %) as well as highly deviated trajectory of the motile cells. In b-CT method at 0-hour incubation, there were no significant discrepancies for spermatozoa categories with intact structural integrity in C (50.05 %), E2 (48.95 %), and E3 (48.25 %). Despite this, C had high deviation of trajectory linearity. E3 samples of a-CT at 0-hour incubation had higher proportion of spermatozoa with intact structural integrity (57.16 %) in relation to E3 samples of b-CT method (48.25 %). It was conclusive that the combined supplementation of GSH (5 mM) and HSP (20 %) in tris-CP media used for extending ejaculates prior CP, resulted in significantly higher CP capacity for ram spermatozoa of ovchepolska pramenka compared to other tris-CP media which contained GS (5 mM) or HSP (20 %). Post-thaw incubation time of 3-hours has increased the number of spermatozoa with damaged structural integrity, affected morphology or hyper-activated motility, regardless of the CP-media or extending method.
Increasing of cryopreserving capacity of ejaculate media for ovchepolska pramenka by utilizing seminal plasma and glutathione
Докторска дисертација одбранета во 2019 година на Факултетот за ветеринарна медицина во Скопје, под менторство на проф. д–р Тони Довенски.
Keywords: ram, cryopreservation, reduced-glutathione, homologous-seminal-plasma